2008
DOI: 10.1523/jneurosci.5493-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Collateral Connections of Striatal Medium Spiny Neurons Are Disrupted in Models of Parkinson's Disease

Abstract: The principal neurons of the striatum, GABAergic medium spiny neurons (MSNs), are interconnected by local recurrent axon collateral synapses. Although critical to many striatal models, it is not clear whether these connections are random or whether they preferentially link functionally related groups of MSNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
479
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(504 citation statements)
references
References 56 publications
(66 reference statements)
24
479
1
Order By: Relevance
“…This result suggests that iSPN neurons are more sensitive to the transcriptional regulation of VGAT by NO than dSPNs. In line with this idea, we and others have previously found that axon collaterals between SPNs of the two projection systems are not symmetrical because iSPNs profoundly innervate and efficiently inhibit dSPNs (14,20,21). Together with these studies, our experiments suggest that NO signaling regulates motor behavior and action selection by maintaining the normal function of axon collaterals.…”
Section: Dopamine Signaling Regulates Striatal Cgmp and Collateral Vgatsupporting
confidence: 87%
See 2 more Smart Citations
“…This result suggests that iSPN neurons are more sensitive to the transcriptional regulation of VGAT by NO than dSPNs. In line with this idea, we and others have previously found that axon collaterals between SPNs of the two projection systems are not symmetrical because iSPNs profoundly innervate and efficiently inhibit dSPNs (14,20,21). Together with these studies, our experiments suggest that NO signaling regulates motor behavior and action selection by maintaining the normal function of axon collaterals.…”
Section: Dopamine Signaling Regulates Striatal Cgmp and Collateral Vgatsupporting
confidence: 87%
“…3 F and G), suggesting that GABAergic synapses were not being redistributed. GABAergic synapses onto SPNs are derived from one of three sources: fast-spiking (FS) interneurons, neuronal nitric oxide synthase (nNOS)-positive interneurons, and collateral SPN synapses (14,15). FS interneurons make perisomatic synapses that give rise to largeamplitude IPSCs.…”
Section: ) (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…41 Second, selectivity of somatotopic neuronal responses to peripheral stimulation is blurred in cortical motor areas 42,43 and basal ganglia nuclei. 44 Third, corticostriatal activity is biased towards activation of striatal neurons in the indirect circuit, 45 which, in association with increased collateral inhibition from medium spiny neurons, 46 leads to globus pallidus pars externa (GPe) inhibition …”
Section: Motor Features Akinesiamentioning
confidence: 99%
“…To model the inhibition generated by the striatal inhibitory microcircuits, we modified the channel kinetics of unitary GABAergic synaptic conductances to mimic different inhibitory inputs ( Fig. 3B) (18,19): (i) FS-mediated perisomatic inhibition (FS GABA), (ii) SPN and LTS interneuron-mediated dendritic inhibition with fast kinetics (fast GABA), and (iii) NPY-expressing neurogilaform (NPY-NGF) interneuron-mediated dendritic inhibition with slow kinetics (slow GABA) (26,39,40). We first monitored the membrane potential perturbations (ΔVm) caused by inhibition with different delay timing (Δt Inh ) on plateau potentials (Fig.…”
Section: Model Predicts a Unique Spatiotemporal Window For Cell-type-mentioning
confidence: 99%